Broad and Region-Specific Impacts of the Synthetic Cannabinoid CP 55,940 in Adolescent and Adult Female Mouse Brains - Leishman, Emma; Murphy, Michelle N.; Murphy, Michelle I.; Mackie, Ken; Bradshaw, Heather B. (Frontiers in Molecular Neuroscience, 2018)
Relative to Δ9-tetrahydrocannabinol (THC), the synthetic cannabinoid CP 55,940 (CP) is significantly more potent and efficacious at cannabinoid receptors, the primary targets for endogenous cannabinoids (eCBs). eCBs belong to a large, interconnected lipidome of bioactive signaling molecules with a myriad of effects in optimal and pathological function. Recreational use of highly potent and efficacious synthetic cannabinoids is common amongst adolescents, potentially impacting brain development. Knowledge of the molecular outcomes of synthetic cannabinoid use will be important to develop more targeted therapies for synthetic cannabinoid intoxication and to prevent long-term disruption to the CNS. Here, we test the hypothesis that CP has age and region-dependent effects on the brain lipidome. Adolescent (post-natal day (PND) 35 and PND 50) and young adult female mice were given either an acute dose of CP or vehicle and brains were collected 2 hours later. 8 brain regions were dissected and levels of ~80 lipids were screened from each region using HPLC/MS/MS. CP had widespread effects on the brain lipidome in all age groups. Interestingly, more changes were observed in the PND 35 mice and more were reductions in a lipid’s concentration, including region-dependent lowering of eCB levels. CP levels were highest in the cortex at PND 35, the hippocampus at PND 50, and in the cerebellum in the adult. These data provide novel insights into how high-potency, synthetic cannabinoids drive different, age-dependent, cellular signaling effects in the brain.